The world detective : a life in words from serendipity to selfie - Simpson, John. (London : Abacus, 2016)
In The Word Detective, an intensely personal memoir and a joyful celebration of English, Simpson weaves a story of how words come into being (and sometimes disappear), how cultures shape the language we use, and how we cope when words fail us. Throughout, he enlivens his narrative with lively excavations and investigations of individual words -- from deadline to online and back to 101 (yes, it's a word) -- all the while reminding us that the seemingly mundane words (can you name the four different meanings of ma?) are often the most interesting ones. A brilliant expedition through the world of words, The Word Detective will delight, inspire, and educate any lover of language.
Serendipity, perhaps.--Lexicography 101.--Marshallers of words.--The longest way round.--Uneasy skanking.--Shark-infested waters.--OED redux.--The tunnel and the vision.--Gxddbov xxkxzt pg ifmk.--At the top of the crazy tree.--Shenanigans online.--Flavour of the month.--Becoming the past.
Includes index.
Keywords: SIMPSON, J. A., 1953.; OXFORD ENGLISH DICTIONARY; LEXICOGRAPHERS; ENGLISH LANGUAGE -- LEXICOGRAPHY; GREAT BRITAIN